The Effect of Reading & Writing Literacy Awareness Elementary Education Teachers on the Reading and Writing Literacy Ability of High-Grade Students - Alfulaila, Noor (JURNAL AL-TANZIM, 2022)
The background of this research is the low reading literacy ability of high grade students in Banjarmasin. The low reading ability is thought to have an effect on student achievement. This is indicated by the results of student learning achievement which is still low. The aims of the study were; 1) to determine the reading literacy ability; 2) to determine the level of learning achievement; and 3) to determine the effect of reading literacy ability on the learning achievement of high-class students in Banjarmasin. The research design used survey quantitative research with research samples of high-class students in Banjarmasin. Data analysis using simple linear regression test. The results showed that; 1) students' reading literacy ability was quite adequate at 67.53%; 2) student learning achievement was classified as very good at 81%; and 3) there was a significant effect of 5.4% between reading literacy ability and achievement student learning.